MS 2809:2025 Authentication of products using chemometric techniques - Yahya, Padillah; Borhan, Fakheezah; Othman, Nurul I'zzati; Ch'ng, Ai Ying; Radzi, Khairuddin; Razali, Rohaieza; Zubaidah, Raja; Sulaiman, Siti Farehah; Tunggal, Mohd Fazir; Ali, Norazlina; Helmy, Mohamad Habeeb; Muhamad, Mohd Asrul Hafiz; et al. (Jabatan Standard Malaysia, 2025)
This document provides detailed descriptions of chemometric techniques for authentication of products. This document recommends chemometric techniques using mathematical modelling and statistical analysis to extract information and analyse chemical analytical data where interrelationships among samples are unravelling as pattern recognition. The procedure in this document can be applied to chemical datasets that generate quantitative measurements on samples. The underlying relationship between variables is developed via a chemometric software computational model. Users can choose any chemometric software with techniques as specified in this standard. NOTE Chemical data is often collected from instruments such as chromatography, spectroscopy and spectrometry.